The power struggle between the military junta and democracy in Myanmar - Shahruddin, Amirah Syuhada; Fathil, Fauziah (IIUM Press, 2023)
Ever since the first coup by the military forces in 1962, Myanmar has stood out among the Southeast Asian nations due to the prolonged political turmoil between the ever-powerful junta and the rising forces of the people, assisted by the National League for Democracy (NLD) party who demanded democracy. These clashes have profoundly affected the country’s socio-economic and politics for decades. Hence, to find the root of this long-ongoing conflict, this paper examines the historical timeline of the friction between the two factions, the military junta (Tatmadaw), and the general population from the post-independent years until now. The study analyses various aspects, including the ethnic tension, the formation of Tatmadaw, the events leading to three military coups, and the people with their multiple uprisings. This paper also sheds light on the leading party, NLD, especially on the central figure, Aung San Suu Kyi, who became the voice of democracy. Overall, this study mainly used the library research method and a content-analysis approach to gather information and assess the dynamic relations between the two forces and how the power struggle remains well into the 21st century.